1993
DOI: 10.2466/pr0.1993.73.2.542
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Need for Cognition and Modern Racism

Abstract: Survey results from 59 college students indicated that those low in need for cognition evidenced higher racial prejudice than respondents high in need for cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 3 publications
3
15
0
Order By: Relevance
“…This finding is consistent with past findings that racially tolerant individuals are psychologically healthy (Allport, 1950;Grossarth-Maticek, Eysenck and Vetter, 1989;Jahoda, 1961;Pettigrew, 1981). Second, I discovered maladaptive patterns of psychosocial personality style associated with prejudiced individuals, a finding consistent with those of Adorno et al (1950), Gough andBradley (1993), andWaller (1993). Blatant racists are wounded individuals with markedly poor internal integration.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…This finding is consistent with past findings that racially tolerant individuals are psychologically healthy (Allport, 1950;Grossarth-Maticek, Eysenck and Vetter, 1989;Jahoda, 1961;Pettigrew, 1981). Second, I discovered maladaptive patterns of psychosocial personality style associated with prejudiced individuals, a finding consistent with those of Adorno et al (1950), Gough andBradley (1993), andWaller (1993). Blatant racists are wounded individuals with markedly poor internal integration.…”
Section: Resultssupporting
confidence: 61%
“…They also found indications of disturbed family relationships in intolerant individuals. Waller (1993) found cognitive rigidity among intolerant individuals.…”
mentioning
confidence: 99%
“…Recent research on conservatism was conducted primarily within a cognitive framework, using measures that focus on intra-individual processes, such as cognitive style (Tetlock, 1984;Tetlock, Bernzweig, & Gallant, 1985) and need for cognition (Waller, 1993). In general, we agree with this cognitive approach.…”
Section: Theoretical Framework Of Conservatismsupporting
confidence: 60%
“…Also, NFC is negatively correlated with racial prejudice (e.g., Waller, 1993) and support for punishing criminals (Sargent, 2004). In relation to this, Sargent (2004) found that AC mediates the effect of NFC on punitiveness.…”
Section: Attributional Complexity and Need For Cognitionmentioning
confidence: 98%